Pandemic as a prerequisite of discrimination of the senior citizens - Tarusina Nadezhda Nikolaevna; Sokolov Aleksandr Vladimirovich; Isaeva Elena Aleksandrovna (SHS Web of Conferences, 2021)
The objective of the research is to reveal and comprehend the peculiarities of the status (complex of rights of their restrictions) of the citizens in the conditions of pandemic COrona VIrus Disease-19, in particular, of the new category of minorities – people at the age of 65+ years old. The methodological base of the research is the universal, general scientific and specific scientific cognitive methods used by the legal science in the object-subject scope of cognition of the general theory of law. The process of research was focused on the comparativistics, and the historical and legal, comparative and legal, technical and other special methods of scientific cognition were applied. To estimate the situation the empiric data of the three sociological researches when questioning the dwellers of Yaroslavl Region were used. The results of the research of the comfort level of the senior citizens in the specified conditions obtained during the analysis of the legislation, and its practical application and the data of sociological researches became the conclusions that the prohibited activities do not only protect from risks but also create the new ones – intellectual, psychic and physical moments. The authors believe that as the emergency situations cannot be settled by the current pandemic, the state has to correct its regulatory and legal and managerial positions taking into account the own experience and recommendations of the specialists, including those regarding the status of a new group of minorities that is the citizens at the age of 65+ years old. The novelty of the research was stipulated by the formulated recommendations to form the optimal regulatory and legal limits of the positive discrimination of the mentioned category of citizens.